The effect of the “Transcarpathia” Free Economic Belt on the investment activities of the region and its development of foreign trade relations - Koval, Katalin (Acta Agraria Debreceniensis, 2011)
The article analyses the figures of foreign investments and their territorial distribution and their change due to the impact of the “Transcarpathia” Free Economic Belt. The article studies the consequences of the liquidation of the “Transcarpathia” Free Economic Belt and the issue of restoring allowances that formerly existed on its territory. The Free Economic Belt that was founded in 1998 and its customs and tax allowances invoked the settlement of affiliated firms of several world corporations, like the “Eurocar”, the “Yadzaki”, or the “Jabil”. However in 2005 the government of that time repealed all allowances granted by the “Transcarpathia” Free Economic Belt, and due to this the increasing dynamics of the amount of foreign stocks which was penetrating into the economy of Transcarpathia started to decrease. Many companies halted their work which went alongside with closing-down several thousands of workplaces. The working “Transcarpathia” Free Economic Belt had a positive effect on the social and economic indices of the region, so discussions regarding its restoration have already been started between the president of Ukraine and the governor of the region.